Nonlinear bubble dynamics in cryogenic two-phase flow under ultrasonic excitation considering mass transfer - Jin Zhang; Yu Zhang; Yong Chen; Xiaobo Rui; Congren Zheng; Yu Wu; Jie Yang; Hexin Gao; Lei Qi (Ultrasonics Sonochemistry, 2025)
Bubble dynamics under ultrasonic excitation is the theoretical basis for ultrasonic measurement of gas-liquid two-phase flow. In cryogenic two-phase flow, bubble oscillation will be affected by vapor mass transfer due to the presence of liquid vapor. This article combines the ideal gas-liquid vapor assumption and the cryogenic fluid state equation to establish a numerical model of cryogenic bubble dynamics under ultrasonic excitation considering vapor mass transfer. The influences of ultrasonic excitation frequency, amplitude, and ambient pressure on bubble oscillations are analyzed through numerical calculations. The results indicate that considering vapor mass transfer, bubble resonant frequency and the variation of temperature change increases, while the variation of radius change decreases. When the ambient pressure is low and the ultrasonic excitation frequency is equal to the bubble’s resonant frequency, the vibration of bubbles exhibits obvious nonlinear characteristics, and it may cause bubble collapses at higher excitation amplitudes. By establishing a finite volume simulation model and comparing it with numerical calculations, the accuracy of the theoretical model is verified.